Peramalan Jumlah Penerbitan Surat Izin Mengemudi Berjenis C di Satlantas Polresta Padang dengan Menggunakan Metode ARIMA - Yeni, Annisa Septi (Journal of Mathematics UNP, 2024)
A driving license (SIM) is an important indicator of traffic planning and management in a given area. Therefore, we will forecast the number of C-SIMs issued in the future to help the Polri agency plan traffic policy authority, allocate power resources, and manage infrastructure effectively. The study aims to apply the ARIMA methodology in analyzing and predicting the number of C-IDs issued for the period from July 2024 to June 2025. The study utilizes historical data on the number of C-SIMs issued from January 2019 to June 2024. The results showed that the ARIMA (1,1,1) model produced a prediction of the number of SIM C issuances at the Padang Police Traffic Unit for the period July 2024 to June 2025, with the estimated number ranging from 1900 to 1578.